Gender-Smart Investing for Food Systems Transformation Webinar Report - Koge, Jessica; Derenoncourt, Marie Ena (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Dissemination workshop report for the webinar to launch the “Strategic roadmap on mainstreaming gender-smart investing to scale climate-smart agriculture in sub-Saharan Africa” brief. The webinar was held virtually on October 11, 2022. Presentations from CGIAR, GIZ, public and private investors, ecosystem enablers, and Small and Medium Enterprises (SMEs) of different scales operating in Tanzania, Kenya, Zambia, and Senegal highlighted recent developments at the nexus of gender and climate finance and proposed solutions to mainstream gender-smart investing for innovative and inclusive food systems transformation. The presentations were followed by two concurrent breakout sessions, one on the realities for the supply of capital with a gender lens to agricultural value chain actors, and the other on the challenges of, and opportunities for, raising capital by climate innovators.